Archaeology and Islam in Indonesia - Wood, Michael (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2008)
Some Indonesian archaeologists, however, have focused on the nation's Islamic past. Uka Tjandrasasmita is one of Indonesia's leading archaeologists and is largely behind the writing of Volume III of the Sejarah Nasional Indonesia, the national history that was the